2006
DOI: 10.1097/01.rli.0000188359.72928.0f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gadolinium-BOPTA and Ferucarbotran-Enhanced Three-Dimensional T1-Weighted Dynamic Liver Magnetic Resonance Imaging in the Same Patient

Abstract: Feru-enhanced T1w dynamic images demonstrated significant signal increases for liver, vessels, and spleen but overall lower signal intensities than Gd-BOPTA. The dynamic signal courses of ferucarbotran were similar to that of Gd-BOPTA during ll perfusion phases except in the spleen. Thus, it may be possible to detect typical enhancement pattern of focal liver lesions with Feru-enhanced dynamic T1w MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Most FNHs and FNH‐like lesions are stable in size, with some even diminishing, and only about 10% of these tumors show a slight increase in size, although a few cases showed HCC arising in a background of FNH or co‐existent FNH and HCC 9,10,12–17 . We found that 53 of 55 FNHs and FNH‐like lesions observed without surgical resection or RFA were stable in size or even regressed, with no evidence of malignant transformation.…”
Section: Discussionmentioning
confidence: 61%
“…Most FNHs and FNH‐like lesions are stable in size, with some even diminishing, and only about 10% of these tumors show a slight increase in size, although a few cases showed HCC arising in a background of FNH or co‐existent FNH and HCC 9,10,12–17 . We found that 53 of 55 FNHs and FNH‐like lesions observed without surgical resection or RFA were stable in size or even regressed, with no evidence of malignant transformation.…”
Section: Discussionmentioning
confidence: 61%
“…Resovist ® (SHU 555A, Bayer Schering AG, Berlin, Germany), an MRI contrast agent already approved for clinical use in Europe, Japan and Australia, is organ-specific and used for liver imaging [41-43]. It consists of superparamagnetic iron oxide (SPIO) nanoparticles (4-6 nm) [44] coated with carboxydextran (mean hydrodynamic diameter 60 nm), which is accumulated by phagocytosis in von Kupffer cells.…”
Section: Methodsmentioning
confidence: 99%
“…Resovist, or SHU 555A (Schering), an MR imaging contrast agent already approved for clinical use in Europe, Japan, and Australia, is organ-specific and is used for liver imaging (20)(21)(22). It consists of SPIO nanoparticles (4 -6 nm) (23) coated with carboxydextran (mean hydrodynamic diameter, 60 nm), which is accumulated by phagocytosis in Kupffer cells.…”
Section: Contrast Media and Cell Labelingmentioning
confidence: 99%